2006
DOI: 10.1007/s10803-006-0171-5
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Single and Multiple Emotions in High-functioning Children with Autism

Abstract: This study examined emotional awareness in children with autism. Twenty-two high functioning children with autism (mean age 10 years and 2 months) and 22 typically developing children, matched for age and gender, were presented with the four basic emotions (happiness, anger, sadness and fear) in single and multiple emotion tasks. Findings suggest that children with autism have difficulties identifying their own emotions and less developed emotion concepts (which causes an impaired capacity to differentiate bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(98 citation statements)
references
References 25 publications
4
88
0
1
Order By: Relevance
“…The neurophysiological basis of this ability, often referred to as mentalizing, can be demonstrated in a network of regions, which shows reduced activation in this group (see Frith & Frith, 2006, for a review). However, much less is known of how these high-functioning individuals experience their own bodily and emotional states, although a number of studies suggest that this experience is abnormal, with impaired emotional awareness being frequently reported (Ben Shalom et al, 2006;Hill, Berthoz, & Frith, 2004;Hurlburt, Happé, & Frith, 1994;Rieffe, Meerum Terwogt, & Kotronopoulou, 2006). This study aimed to increase this knowledge by investigating emotional awareness in HFA/AS.…”
Section: Discussionmentioning
confidence: 97%
“…The neurophysiological basis of this ability, often referred to as mentalizing, can be demonstrated in a network of regions, which shows reduced activation in this group (see Frith & Frith, 2006, for a review). However, much less is known of how these high-functioning individuals experience their own bodily and emotional states, although a number of studies suggest that this experience is abnormal, with impaired emotional awareness being frequently reported (Ben Shalom et al, 2006;Hill, Berthoz, & Frith, 2004;Hurlburt, Happé, & Frith, 1994;Rieffe, Meerum Terwogt, & Kotronopoulou, 2006). This study aimed to increase this knowledge by investigating emotional awareness in HFA/AS.…”
Section: Discussionmentioning
confidence: 97%
“…Bolte and colleagues (2006), working with individuals with autism, observed brain activation changes following treatment in brain regions associated with visuospatial and facial processing. These results are remarkable given the developmental and longstanding nature of these disorders, which are likely to have limited any awareness of emotional material from an early age (Hill et al, 2004;Leonard et al, 2002;Rieffe et al, 2007).…”
Section: Remediation Of Deficits In Emotion Perception In Other Clinimentioning
confidence: 97%
“…It has an impact at both intrapersonal and interpersonal levels and has been linked to socio-affective deficits such as a lack of empathy (Guttman and Laporte 2002). The few studies that have examined alexithymia in children with ASD have found that, similarly to adults (Berthoz and Hill 2005), alexithymia is more prevalent among children with ASD than among TD children (Griffin et al 2015;Rieffe et al 2007). In one study it was found that the facial expressions of individuals with higher levels of alexithymia appeared to be odder than of those with lower levels (Brewer et al 2016).…”
Section: Emotional Response Incoherence In Asd and The Role Of Alexitmentioning
confidence: 99%